Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Singh, Suresh Prasad; Jain, Abhinav; Anantha, M.S.; Tripathi, Santosh; Sharma, Subarna; Kumar, Santosh; Prasad, Archana; Sharma, Bhawana; Karmakar, Biswajit; Bhattarai, Rudra; Das, Sankar Prasad; Singh, Shravan K.; et al. (Springer, 2017)
# Aims